Student solutions manual to accompany technical mathematics with calculus - Ewen, Dale 1941-; Gary, Joan S.; Trefzger, James E. (Pearson Education, Inc., 2005)
seful for 2-3 term courses in Technical Math, including Calculus. This 2nd edition provides comprehensive coverage of the mathematics needed by students in technical career fields or engineering technology programs. It includes technology examples and applications that are integrated throughout the text, supported by over 8400 exercises